A “Textilic Reading” of Eight Stories from Gaza - Naor, Sigal (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2025)
This article discusses eight short stories written by writers from Gaza and published in Amputated Tongue. A linear, organized interpretative reading in the translated stories from Gaza might further add to their appropriation by the Hebrew and Israeli language and culture. Thus, this article offers a “textile reading” of the stories. The “textile reading” is based on the Homeric story “Procne and Philomela,” in which the latter secretly brings her sister an embroidered fabric which testifies to her rape by the sister’s husband, Tereus. The way in which Procne reads her sister’s story in the embroidered symbols is not textual, but “textilic.” Similarly, this article attempts to turn the stories from Gaza from text to textile, by “tearing out” a sign, a visual image central to all stories, the image of the hand. In order to decipher this image, the article partially leans on the iconographic model of Erwin Panofsky. At first, the first stage of the model is enacted, and the pre-iconographic stage and the descriptions of the hand are scrutinized. Then, in the iconographic analysis stage, the image of the hand is scrutinized in reference to the larger arena of contemporary Palestinian art.